2017
DOI: 10.1039/c6ob02335e
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of constraints imposed by modified nucleoside triphosphates with protein-like side chains for use in in vitro selection

Abstract: Successful selection of modified DNAzymes depends on the potential for modified nucleoside triphosphates (dNTPs) to replace their unmodified counterparts in enzyme catalyzed primer extension reactions and, once incorporated, to serve as template bases for information transfer prior to PCR amplification. To date, the most densely modified DNAzymes have been selected from three modified dNTPs: 8-histaminyl-deoxyadenosine (dATP), 5-guanidinoallyl-deoxyuridine (dUTP), and 5-aminoallyl-deoxycytidine (dCTP) to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Theu tility of DNAf or these applications stems from its precisely controllable sequence composition and base pairing, which enables the polymerase chain reaction (PCR) amplification of specific polymers and/or the control of their assembly into higher order structures;h owever their physicochemical properties are limited to those possessed by the four nucleobases,s ugar, and phosphate.T hus,t ot ake full advantage of the precise sequence composition available with DNA, modifications have been sought that may be introduced to one or more of the triphosphates without interfering with their polymerase recognition. Themost success has been achieved with nucleobase modifications, [11][12][13][14][15][16][17][18] which have been used to develop aptamers with protein-like properties, [19,20] or to introduce sites for the attachment of other moieties by click chemistry. [21][22][23][24][25] However this approach is mostly limited to pyrimidine modifications,and the modified oligonucleotides themselves are not well recognized by polymerases,p reventing their production via PCR-mediated amplification.…”
mentioning
confidence: 99%
“…Theu tility of DNAf or these applications stems from its precisely controllable sequence composition and base pairing, which enables the polymerase chain reaction (PCR) amplification of specific polymers and/or the control of their assembly into higher order structures;h owever their physicochemical properties are limited to those possessed by the four nucleobases,s ugar, and phosphate.T hus,t ot ake full advantage of the precise sequence composition available with DNA, modifications have been sought that may be introduced to one or more of the triphosphates without interfering with their polymerase recognition. Themost success has been achieved with nucleobase modifications, [11][12][13][14][15][16][17][18] which have been used to develop aptamers with protein-like properties, [19,20] or to introduce sites for the attachment of other moieties by click chemistry. [21][22][23][24][25] However this approach is mostly limited to pyrimidine modifications,and the modified oligonucleotides themselves are not well recognized by polymerases,p reventing their production via PCR-mediated amplification.…”
mentioning
confidence: 99%
“…Despite the fact that 5‐CldUTP residues were described to pair with dATP but also with dGTP, we observed no significant misincorporation in place of 5‐CldUTP residues (Section S7). This is consistent with a recent work in which the base‐pairing abilities of oligonucleotides incorporating one or three modified nucleosides were investigated and showed correct incorporation of modified dNTPs …”
Section: Resultsmentioning
confidence: 77%
“…Previously, we showed that the dC aa s greatly stabilize complementary interactions, which we anticipated would constitute an advantage in terms of substrate recognition and would offset the slightly destabilizing effects of the dA im . 72 Nevertheless, we also recognized that these modifications would limit the ability to alter the 3′-guide arm sequence. To test this, we replaced the dA im in the guide arm with dG; the resulting DNAzyme had limited yet detectable activity against the complementary substrate (∼20%), and very little activity against the original substrate that would contain a G-U wobble mismatch (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that Sequenase, the enzyme used to prepare Dz7-38-32, inserts 1–3 with high fidelity while Taq recopies the resulting modified strands with equally high fidelity resulting in less than 1% mutation overall. 72 That insertion and read-out result in the selection of a given DNAzyme containing 1–3 , reflects the incontrovertible consequences of semiconservative replication along with Chargaff's rules, which ensure that a modified nucleoside will either be perpetuated through rounds of selection or otherwise irretrievably lost. More importantly, we demonstrated that the enzymatic synthesis of these DNAzymes provides homogeneous species that are as pure as any other enzymatically synthesized DNAzyme or ribozyme.…”
Section: Discussionmentioning
confidence: 99%